Myeloperoxidase Is a Negative Regulator of Phospholipid-Dependent Coagulation - Beckmann, Lennart; Dicke, Christina; Spath, Brigitte; Lehr, Carina; Sievers, Bianca; Klinke, Anna; Baldus, Stephan; Rudolph, Volker; Langer, Florian (Thrombosis and Haemostasis, 2017)
Myeloperoxidase (MPO) is a cationic heme enzyme stored in neutrophilic polymorphonuclear leukocytes (PMNs) that has recently been implicated in inflammatory cell signaling and tissue damage. Although PMNs play a critical role in both innate immunity and vascular thrombosis, no previous study has systematically investigated the effect of MPO on blood coagulation. Here, we show that PMN-derived MPO inhibits the procoagulant activity (PCA) of lipidated recombinant human tissue factor (rhTF) in a time- and concentration-dependent manner that involves, but is not entirely dependent on the enzyme's catalytic activity. Similarly, MPO together with its substrate, H2O2, inhibited the PCA of plasma microvesicles isolated from lipopolysaccharide (LPS)-stimulated whole blood, an effect additive to that of a function blocking TF antibody. Treatment of whole blood with LPS or phorbol-myristate-acetate dramatically increased MPO plasma levels, and co-incubation with 4-ABAH, a specific MPO inhibitor, significantly enhanced the PCA in plasma supernatants. MPO and MPO/H2O2 also inhibited the PCA of activated platelets and purified phospholipids (PLs), suggesting that modulation of negatively charged PLs, i.e., phosphatidylserine, rather than direct interference with the TF/FVIIa initiation complex was involved. Consistently, pretreatment of activated platelets with MPO or MPO/H2O2 attenuated the subsequent binding of lactadherin, which specifically recognizes procoagulant PS on cell membranes. Finally, endogenously released MPO regulated the PCA of THP1 cells in an autocrine manner dependent on the binding to CD11b/CD18 integrins. Collectively, these findings indicate that MPO is a negative regulator of PL-dependent coagulation and suggest a more complex role of activated PMNs in haemostasis and thrombosis.
Keywords: myeloperoxidase; leukocyte activation; microparticles; integrins